Minimal access nipple-sparing mastectomy – the current European landscape - Pluta, Piotr; Rathat, Gauthier; Blay, Lydia; Gentilini, Oreste Davide; Huber, Daniela Emanuela; Daniel, Martinez; Guillermo, Peralta; Rami J., Younan; Glenn, Vergauwen; Antonio, Toesca (Menopause Review/Przegląd Menopauzalny, 2025)
Minimal access nipple-sparing mastectomy (M-NSM), performed with endoscopic systems or with surgical robot assistance, is a novel alternative to the classic approach to nipple-sparing mastectomies. Leading advancements in M-NSM have primarily come from Asia. We gather experts’ opinions from six European countries to establish the current status of M-NSM in Europe. An eight-question survey was designed to explore M-NSM’s historical background and current standing in various local settings. We collected data from 6 European countries, including Italy, Spain, France, Switzerland, Belgium, and Poland. The number of centers offering M-NSM procedures in each reported country ranges 1–9. The number of procedures performed annually in four centers exceeds 10. In all reported countries, current national breast cancer recommendations do not include M-NSM, and this procedure is not explicitly covered by any of the national health care providers. All experts have indicated the need for training in M-NSM surgery as a primary way to incorporate these techniques as a standard procedure. Minimal access nipple-sparing mastectomy is still a tool used by a narrow group of specialists in Europe. The main obstacle to broader implementation remains the extra cost of M-NSM, which requires reimbursement from the health care providers. Training courses, data collection, and demonstration of its benefits are the key to promoting M-NSM among breast surgeons and patients.